2023
DOI: 10.3389/fonc.2023.1117348
|View full text |Cite
|
Sign up to set email alerts
|

Real-world clinical practice and outcomes in treating stage III non-small cell lung cancer: KINDLE-Asia subset

Abstract: IntroductionStage III non-small cell lung cancer (NSCLC) is a heterogeneous disease requiring multimodal treatment approaches. KINDLE-Asia, as part of a real world global study, evaluated treatment patterns and associated survival outcomes in stage III NSCLC in Asia.MethodsRetrospective data from 57 centers in patients with stage III NSCLC diagnosed between January 2013 and December 2017 were analyzed. Median progression free survival (mPFS) and median overall survival (mOS) estimates with two sided 95% confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…To the best of our knowledge, this is the first population-based study to explore this specific topic. The outcomes of our investigation, which showed no statistically significant effect of RT on OS, align with the findings reported in the KINDLE study, [ 10 , 11 ] as the 95% confidence intervals overlapped; however, it is important to note that the KINDLE study reported a numerically longer median OS for the RT group (42.6 months) compared to the non-RT group (25.4 months), whereas our study found similar OS values in both groups.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first population-based study to explore this specific topic. The outcomes of our investigation, which showed no statistically significant effect of RT on OS, align with the findings reported in the KINDLE study, [ 10 , 11 ] as the 95% confidence intervals overlapped; however, it is important to note that the KINDLE study reported a numerically longer median OS for the RT group (42.6 months) compared to the non-RT group (25.4 months), whereas our study found similar OS values in both groups.…”
Section: Discussionsupporting
confidence: 91%
“…Another RCT for patients with unresectable stage III NSCLC with EGFR mutations showed that erlotinib plus RT significantly improved progression-free survival relative to dCCRT [ 9 ]. A search conducted on PubMed using the terms, “((non-small-cell lung) OR (lung adenocarcinoma)) AND ((locally advanced) OR (stage III)) AND (EGFR mutation) AND ((radiation) OR (radiotherapy)) AND (gefitinib OR erlotinib OR afatinib OR dacomitinib OR osimertinib OR (tyrosine kinase inhibitor ∗ )),” in June 2023 yielded no relevant RCTs, only the observational KINDLE study [ 10 , 11 ]. Given the aforementioned controversy and the limited literature available on this topic, we designed this retrospective cohort study to investigate the efficacy of definitive RT for patients with clinical stage IIIB or IIIC lung adenocarcinoma and EGFR mutations treated with first- or second-generation EGFR TKIs using a population-based approach.…”
Section: Introductionmentioning
confidence: 99%
“… 55 Comparable challenges persist in Central and Eastern European nations, and data from an Asian study showed just 32% of stage III NSCLC cases underwent MDT discussions. 56 , 57 Barriers like infrastructure, logistics, financial limitations, and expert shortages hinder MDT adoption. 58 …”
Section: Variations In Access To New Treatmentsmentioning
confidence: 99%